Peran kelekatan dengan orangtua dan kecerdasan emosional terhadap kesejahteraan psikologis siswa SMA (Jurnal Psikologi Udayana, 2023)
Psychological well-being is a condition when the individual is not under stress or other mental health problems. The existence of psychological well-being can improve the adolescents mental health and help the adolescents function optimally. Proper consideration is needed for the psychological well-being of adolescents to be enhanced. The factors to consider include parent attachment and emotional intelligence. This study is a quantitative study to determine the role of parent attachment and emotional intelligence for the psychological well-being of high-school student. A total of 165 students of class X, XI, and XII at one of the state high schools in Denpasar were the respondents in this study using stratified random sampling. Psychological Well-Being Scale with a reliability of 0,915, the Parent Attachment Scale with a reliability of 0,935, and a Scale of Emotional Intelligence with a reliability of 0,845 as the measurement tools that used. The multiple regression test revealed F=41,808, p